AN ENCOURAGING STRATEGY IN PEER CORRECTION (World Science, 2019)
The purpose of the article is to introduce a strategy in the peer correction. Any correction of the mistake being reluctantly welcomed is usually accepted with a sense of disfavor. Peer correction in speaking activity is no exception. To turn this tedious process into an attractive one we have developed a relatively new strategy. Peer correction in writing activity has long been practiced. Learners enjoy discovering each other’s mistakes in essays, spelling or grammar tests, etc. But correcting speaker’s errors being rarely carried out has gradually almost been forgotten. The paper introduces a new concept in peer correction involving a point system. The students actively participating in a correction process are praised with a surplus point for a corrected mistake, which is further taken into account. The strategy has proved to be a motivating one in teaching English as a foreign language.